Physics ContributionsImpact of interfraction seroma collection on breast brachytherapy dosimetry – a mathematical model - Bhatt, Aashish; Sowards, Keith; Bhatt, Geetika; Freeman, Andrew; Dragun, Anthony (Journal of Contemporary Brachytherapy, 2012)
Purpose : Balloon brachytherapy is a widely accepted modality for delivery of accelerated partial breast irradiation (APBI). Our hypothesis was that inter-fraction seroma collection around the balloon surface would have an adverse effect on dosimetry of the target. Material and methods: This is a dosimetric re-planning study using two volumetric models (30 cc and 45 cc) in a Contura ® multi-lumen balloon (MLB) catheter. In a previously treated patient, two customized baseline plans were generated using multiple channels of the Contura ® catheter prescribed to the Planning Target Volume Evaluation (PTV_Eval). Symmetric expansions of 1.0 mm (0-9 mm) increments around the balloon surface were performed to simulate a “Virtual Seroma” (VS) accumulation for both balloon volumes and plans were obtained for each expansion using Eclipse Brachyvision ™ . An analysis of these plans was then performed to evaluate the effect of seroma accumulation on dosimetric parameters of V100 and V90. Results : 20 plans were generated and analyzed (10 plans for each balloon volume), representing VS of 6.0-66.0 cc. There was a commensurate decrease in the dose delivered to the PTV_Eval V100 and V90 (as defined by the original treatment plan) with increasing VS accumulation leading to a sub-optimal coverage of the PTV_Eval. For 30 cc MLB catheter, V100 decreased by 1.4% and V90 decreased by 0.9% for every 1 cc of VS. For 45cc MLB catheter, V100 decreased by 1.3% and V90 decreased by 1.15% for every 1.0 cc accumulation of VS. Conclusions : Balloon catheter-tissue adherence ensures daily dose delivery to the planned PTV_Eval. Accumulation of seroma, hematoma or air between HDR fractions can significantly impact PTV_Eval dosimetry. Vacuum-port aspiration prior to delivery of each fraction, if available, should be considered to minimize the risk of geographic under dosing.